Leadership and leadership development within the profession of physiotherapy in Ireland. (2nd January 2017) - McGowan, Emer; Stokes, Emma
ABSTRACT: Background : Health service reform, physiotherapy graduate unemployment, and the impending introduction of state regulation mean that physiotherapists in Ireland today are facing many challenges. Leadership is needed to ensure that the profession will be able to adapt to the demands and inevitable changes ahead. Objective : To investigate the perceptions of physiotherapists in Ireland of leadership and leadership characteristics, and to explore their participation in leadership development training. Methods : In this cross-sectional nationwide study, an Internet-based survey was administered via e-mail to members of the Irish Society of Chartered Physiotherapists (n = 2, 787). Results : There were 615 responses to the survey. A high proportion of respondents (74.0%) perceived themselves to be a leader. Factors associated with self-declaration as a leader were time since graduation, highest qualification attained, and leadership training. Leadership training was also associated with placing greater importance on achieving a leadership position. Some form of leadership training had been completed by 41.5% of respondents. Communication and professionalism were the most highly rated leadership characteristics in all three settings. Conclusion : Physiotherapists who have had leadership training were more likely to perceive themselves to be leaders. Leadership training may support physiotherapists to assume leadership roles both clinically and nonclinically.